Global CpG DNA Methylation Footprint in Kaposi’s Sarcoma - Journo, Guy; Ahuja, Anuj; Dias-Polak, David; Eran, Yonatan; Bergman, Reuven; Shamay, Meir (Frontiers in Cellular and Infection Microbiology, 2021)
Kaposi’s sarcoma-associated herpesvirus (KSHV), also familiar as human herpesvirus 8 (HHV-8), is one of the well-known human cancer-causing viruses. KSHV was originally discovered by its association with Kaposi's sarcoma (KS), a common AIDS-related neoplasia. Additionally, KSHV is associated with two B-lymphocyte disorders; primary effusion lymphoma (PEL) and Multicentric Castlemans Disease (MCD). DNA methylation is an epigenetic modification that is essential for a properly functioning human genome through its roles in chromatin structure maintenance, chromosome stability and transcription regulation. Genomic studies show that expressed promoters tend to be un-methylated whereas methylated promoters tend to be inactive. We have previously revealed the global methylation footprint in PEL cells and found that many cellular gene promoters become differentially methylated and hence differentially expressed in KSHV chronically infected PEL cell lines. Here we present the cellular CpG DNA methylation footprint in KS, the most common malignancy associated with KSHV. We performed MethylationEPIC BeadChip to compare the global methylation status in normal skin compared to KS biopsies, and revealed dramatic global methylation alterations occurring in KS. Many of these changes were attributed to hyper-methylation of promoters and enhancers that regulate genes associated with abnormal skin morphology, a well-known hallmark of KS development. We observed six-fold increase in hypo-methylated CpGs between early stage of KS (plaque) and the more progressed stage (nodule). These observations suggest that hyper-methylation takes place early in KS while hypo-methylation is a later process that is more significant in nodule. Our findings add another layer to the understanding of the relationship between epigenetic changes caused by KSHV infection and tumorigenesis.